2017
DOI: 10.5625/lar.2017.33.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Over-expression of myosin7A in cochlear hair cells of circling mice

Abstract: Circling mouse (C57BL/6J-cir/cir) deleted the transmembrane inner ear (Tmie) gene is an animal model for human non-syndromic recessive deafness, DFNB6. In circling mouse, hair cells in the cochlea have degenerated and hair bundles have become irregularity as time goes on. Tmie protein carries out a function of the mechanoelectrical transduction channel in cochlear hair cells. Myosin7a (MYO7A) protein has key roles in development of the cochlear hair bundles as well as in the function of cochlear hair cells. To… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…The specimens were incubated in 5% normal goat serum for 1 h at RT to prevent nonspecific labeling. Then, the specimens were incubated with the primary antibody, MYO7A (1:200, ab3481, Abcam, UK), for 1 h at 4 °C [ 44 , 45 , 46 ]. Thereafter, the specimens were washed with PBS three times for five min each time, followed by incubation with a secondary antibody, goat anti-rabbit IgG H&L (Alexa Fluor ® 488; 1:1000, ab150077, Abcam, UK), for 1 h at RT.…”
Section: Methodsmentioning
confidence: 99%
“…The specimens were incubated in 5% normal goat serum for 1 h at RT to prevent nonspecific labeling. Then, the specimens were incubated with the primary antibody, MYO7A (1:200, ab3481, Abcam, UK), for 1 h at 4 °C [ 44 , 45 , 46 ]. Thereafter, the specimens were washed with PBS three times for five min each time, followed by incubation with a secondary antibody, goat anti-rabbit IgG H&L (Alexa Fluor ® 488; 1:1000, ab150077, Abcam, UK), for 1 h at RT.…”
Section: Methodsmentioning
confidence: 99%
“…Myosin7a is critical for the development and arrangement of hair bundles. 23 Cisplatin is known to induce a decrease in Myosin 7a + cell count in rats cochlear organotypic culture. 24 Based on the cochlear organotypic culture, HEI-OC1 cell culture, and CCK-8 detection of cell viability, we found that SFN protected hair cell count, increased Myosin 7a + cell count, prevented HEI-OC1 cell death, and increased cell viability in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…TMIE is likely to collaborate with the MYO7A in the development and maintenance of the stereociliary bundles during the postnatal developmental stages of the cochlea. The expression level of Myo7a increased by 3‐folds in cir/+ and cir/cir against the wild‐type mice at P5, suggesting that the overexpression of Myo7a can be a compensatory mechanism in order to fix the damaged stereocilia in the circling mice in the absence of the TMIE protein 58 …”
Section: Tmie Connects To Other Members In Mechanotransductionmentioning
confidence: 99%